2013
DOI: 10.1111/dote.12028
|View full text |Cite
|
Sign up to set email alerts
|

Patients' intuitive judgments about surveillance endoscopy in Barrett's esophagus: a review and application to models of decision-making

Abstract: SUMMARY Adherence to practice guidelines for endoscopic surveillance of Barrett’s esophagus is equivocal with evidence of underutilization and overutilization. While physicians report strong agreement with and adherence to recommended surveillance endoscopy (esophagogastroduodenoscopy [EGD]) guidelines, less is known about modifiable barriers and facilitators shaping patients’ adherence behaviors. The aim of this study is to conduct a structured literature review of studies exploring patients’ perspectives reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Additional details on methodology and the full interview guide are published elsewhere. 12 All interviews were conducted by either JA or MHL (both female) and were recorded, transcribed, and analyzed for content. We used Atlas.ti 6.2 to facilitate data analysis and management.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional details on methodology and the full interview guide are published elsewhere. 12 All interviews were conducted by either JA or MHL (both female) and were recorded, transcribed, and analyzed for content. We used Atlas.ti 6.2 to facilitate data analysis and management.…”
Section: Methodsmentioning
confidence: 99%
“…17 Furthermore, a recent systematic review of studies describing patients’ perceptions of surveillance EGD found that global judgments about surveillance EGD were often shaped by patients’ perceptions of the prior endoscopy experience. 12 These findings underscore the importance of how patients’ experiences shape their overall judgment of EGD—and intention to adhere to surveillance EGD. However, no previous study has described the salient elements that comprise the patient experience of EGD.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the invasive nature of the surveillance can lead to decreased adherence with the associated decrease of screening effectiveness. Perceived risk plays a role in adherence to recommended surveillance [32], so a tool that better defines risk could contribute to improved adherence. The high cost and limited effectiveness of BE surveillance combined with the benefits of early diagnosis and treatment of EAC create a substantial opportunity to improve cost-effectiveness by stratifying the risk of progression to cancer and targeting more intensive surveillance to those at high risk [27].…”
Section: Overview Of Opportunity For Economic Evaluations To Inform Dmentioning
confidence: 99%
“…13 These are the memories that come to define a healthcare experience and shape a patient's judgment of the care received; therefore, they influence subsequent health behaviors and are worth measuring despite their flaws. 13,14 The novel study by Ottenberg et al, 15 also in this issue of Circulation Cardiovascular Quality and Outcomes, provides further evidence of the need to systematically measure patient experiences. Their qualitative study describes patient experiences from pre-to postimplantation of left ventricular assist devices (LVAD) as destination therapy in patients with advanced heart failure.…”
mentioning
confidence: 98%